PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA SORAYA BEDSHEET CABANG AHMAD YANI PEKANBARU - Pramitari, Jayanti; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study was carried out on a bedsheet Soraya Ahmad Yani PekanbaruBranch, with the aim to determine the quality of service and its influence on customerloyalty sewing services Soraya Ahmad Yani Pekanbaru Branch bedsheet. Thepopulation in this study are customers Soraya bedsheet. By using the samplingtechniques population research, obtained thirty-three samples. Methods andquantitative descriptive performed using simple regression testing techniques.The results showed that the quality provided by Soraya Ahmad YaniPekanbaru Branch bedsheet quite satisfactory, and customer loyalty high enough toSoraya bedsheet. Results of regression testing indicate that factors positivelyinfluence service quality on customer loyalty Soraya Ahmad Yani Pekanbaru Branchbedsheet.Recommendation that the author can give is that Soraya Ahmad YaniPekanbaru Branch bedsheet improve the clarity of the information to the customeraspects, improve customer engagement to the company and to socialize more deeplyto customers regarding the quality of the products supplied by the company.Keywords: Quality of Service and Customer Loyalty